Why do Europeans save? Micro-evidence from the household finance and consumption survey - Charles Horioka; Luigi Ventura (Osaka University, Institute of Social and Economic Research (ISER), 2024)
In this paper, we analyze the saving motives of European households using micro-data from the Household Finance and Consumption Survey (HFCS), which is conducted by the European Central Bank. We find that the rank ordering of saving motives differs greatly depending on what criterion is used to rank them. For example, we find that the precautionary motive is the most important saving motive of European households when the proportion of households saving for each motive is used as the criterion to rank them but that the retirement motive is the most important saving motive of European households if the quantitative importance of each motive is taken into account. Moreover, the generosity of social safety nets seems to affect the importance of each saving motive, with saving for the retirement motive being less important in countries with generous public pension benefits and saving for the precautionary motive being less important in countries with generous health systems. These findings suggest that the retirement motive and the precautionary motive are the dominant motives for saving in Europe partly because social safety nets are not fully adequate. Our finding that saving motives that are consistent with the selfish life-cycle model as well as saving motives that are consistent with the altruism model are important in Europe implies that the two models coexist in Europe, as is the case in other parts of the world. However, our finding that the retirement motive, which is the saving motive that most exemplifies the selfish life-cycle model, is of dominant importance in Europe strongly suggests that this model is far more applicable in Europe than is the altruism model. Moreover, our finding that the intergenerational transfers motive, which is the saving motive that most exemplifies the altruism model, accounts for only about one-quarter of total household wealth in Europe provides further corroboration for this finding.
Keywords: D12; D14; D15; D64; E21; J14; 330; altruism model; bequests; European Central Bank; Household Finance and Consumption Survey; households; household saving; household wealth; inheritances; inter vivos transfers; intergenerational transfers; precautionary saving; retirement; saving; saving motives; selfish life-cycle model; wealth; wealth-to-income ratio